60 GHz digitally controllable and sequentially rotated fed antenna array. Issue 13 (2nd June 2017) - Kim, H.; Lee, Y.; Kim, B.; Baek, K.; Ko, S.; Yang, T.; Lee, J.; Nam, S.
Abstract : Sixteen‐chain sequentially rotated fed antenna array on low‐temperature cofired ceramic substrate is presented. A 60 GHz broadband circular polarised (CP) stacked rectangular patch antenna is implemented as an element. All the feedlines have the same length which is differentiated from conventional T‐junction divider feeder. By this way, several drawbacks of conventional sequential rotated array can be overcome such as phase error occurrence, amplitude mismatch, and axial ratio bandwidth degradation. Moreover, digitally controlled by phase shifters, beamforming performance can be evaluated. The simulated and measured S 11 shows broad bandwidth from 57 to 66 GHz. In addition, the radiation patterns show a peak gain of 17.2 dBi and a wide coverage of ±63°.